Peran Strategis Guru dalam Menanamkan Nilai-Nilai Pendidikan Anti Korupsi pada Siswa SD/MI di Era Digital - Yulia Sukmiyanti; Suryani Suryani; Yuliasari Yuliasari; Wiwi Rodiana; Aisyah Nursyifa; Emi Anggreani Masjur (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2026)
This study aims to examine the strategic role of teachers in instilling anti-corruption educational values in elementary school (SD/MI) students in the digital era. Employing a descriptive qualitative approach, data were collected through in-depth interviews with five SD/MI teachers in Karawang Regency conducted in May 2026. Findings reveal that all informants possess adequate conceptual understanding of anti-corruption education as a character-building process rather than mere knowledge transmission. Teachers perform three principal functions: as behavioral role models, value-based learning facilitators, and collaborative partners with families. Implemented strategies include exemplary conduct, habituation, cross-subject value integration, and utilization of digital media such as educational videos, animations, and interactive quizzes. However, implementation faces significant obstacles, including social media normalizing dishonest behavior, instant-gratification tendencies among students, and weak synergy between schools and family environments. This research affirms that successful internalization of anti-corruption values requires consistent teacher exemplarity, a conducive school ecosystem, robust digital literacy, and sustainable tri-center educational collaboration. Practical implications include the necessity of strengthening teachers' pedagogical competencies in designing character-based learning that is adaptive to the dynamics of the digital era.